If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2 = 8x + 4 Reorder the terms: -2 + 6x = 8x + 4 Reorder the terms: -2 + 6x = 4 + 8x Solving -2 + 6x = 4 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -2 + 6x + -8x = 4 + 8x + -8x Combine like terms: 6x + -8x = -2x -2 + -2x = 4 + 8x + -8x Combine like terms: 8x + -8x = 0 -2 + -2x = 4 + 0 -2 + -2x = 4 Add '2' to each side of the equation. -2 + 2 + -2x = 4 + 2 Combine like terms: -2 + 2 = 0 0 + -2x = 4 + 2 -2x = 4 + 2 Combine like terms: 4 + 2 = 6 -2x = 6 Divide each side by '-2'. x = -3 Simplifying x = -3
| h(t)=-16t^2+63t+4 | | 5+2(x+3)=10-(3x-13) | | P-167=321 | | 180=j-24 | | 125-2x=5x+20 | | -0.875m=0.25 | | 1.7u=0.2 | | =x^2-5x-6 | | K-32=217 | | 0.75y=-0.5 | | 4p+14=11p | | 0.25x+5=9 | | 150+y=879 | | -3=0.4v | | 91=x+52 | | -3=0.4 | | x=(x+1)(x+y) | | 5=0.6w | | 7x+38=-5x-10 | | W+233=319 | | -1.5d=8 | | D-67=23 | | 840=45+f | | y^2-5= | | 314+z=350 | | 0.6x=-4 | | 0.7y=12 | | 12z-12-4z=6-2z+32 | | (x^2-1)(x^2+2x+1)= | | 3x^5y^3+81x^5= | | 5y^2-5= | | -3x^2(4x^2-3x+3)= |